Optimization of fluorescent tools for cell biology studies in Gram-positive bacteria - Catalão, M.J. (2015)
The understanding of how Gram-positive bacteria divide and ensure the correct localization of different molecular machineries, such as those involved in the synthesis of the bacterial cell surface, is crucial to design strategies to fight bacterial infections. In order to determine the correct subcellular localization of fluorescent proteins in Streptococcus pneumoniae, we have previously described tools to express derivatives of four fluorescent proteins, mCherry, Citrine, CFP and GFP, to levels that allow visualization by fluorescence microscopy, by fusing the first ten amino acids of the S. pneumoniae protein Wze (the i-tag), upstream of the fluorescent protein. Here, we report that these tools can also be used in other Gram-positive bacteria, namely Lactococcus lactis, Staphylococcus aureus and Bacillus subtilis, possibly due to optimized translation rates. Additionally, we have optimized the i-tag by testing the effect of the first ten amino acids of other pneumococcal proteins in the increased expression of the fluorescent protein Citrine. We found that manipulating the structure and stability of the 5' end of the mRNA molecule, which may influence the accessibility of the ribosome, is determinant to ensure the expression of a strong fluorescent signal.